Notification to the taxpayer of the suspension of the limitation period as a result of the commencement of fiscal criminal proceedings in the light of performative theory - Brzeziński, Bogumił; Kalinowski, Marek (Studia Iuridica Toruniensia, 2024)
According to Art. 70 § 6 point 1 of the Act of August 29, 1997, the Tax Ordinance, the limitation period for a tax liability does not start, and a started one is suspended on the date of initiation of proceedings in matters of a revenue offence or a revenue petty offence of which the taxpayer has been notified, provided that the suspicion of the offence or petty offence is linked with the non-performance of the obligation. On the other hand, the issue of notifying the taxpayer referred to in that provision has been regulated in Art. 70c of this act. This provision provides that the tax authority competent for the tax obligation, of which the failure to fulfill results in a suspicion of committing a fiscal offence or a fiscal petty offence, shall notify the taxpayer that the period of limitation of the tax obligation has not begun to run or has been suspended and of the fact that the period of limitation will begin to run or will continue to run after the lapse of the suspension period. The subject of the article is the analysis of the latter provision. The authors attempt to determine which authority and how should notify the taxpayer of the non-start or suspension of the limitation period. At the same time, in the process of analysis, an attempt was made to use the theory of performatives. It turned out that the application of this theory to the analysis of the notification of the suspension of the limitation significantly supported the process of interpreting the provision of Art. 70c of the Tax Ordinance Act. It made it easier to select all those elements that are important for determining whether the conventional act, which is the notification of the taxpayer, was made fortuitously, and thus whether it had effects in law. In the light of Art. 70c of the Tax Ordinance, these elements include: a precondition, which is the initiation of penal proceedings, the purpose of which is to determine whether a fiscal offence or a fiscal petty offence has been committed and not to suspend the running of the limitation period; notification by the authority competent to collect the tax of the suspension of the limitation period; including in the notification information that the limitation period has been suspended as a result of the initiation of penal proceedings; preparation of the notification in writing, and then delivery of the letter to the taxpayer in accordance with the rules set out in art. 144 et seq. Tax Ordinance Act; delivery of the notification to the taxpayer no later than 5 years from the end of the tax year in which the tax payment deadline expired; directing the notification directly to the taxpayer. Failure to meet any of these conditions means that the notification act has no effect in the form of a suspension of the limitation period.